Reakcje idiosynkrazji na leki psychotropowe - Szajer, Katarzyna; Grzywa, Anna; Śpila, Bożena (Current Problems of Psychiatry, 2012)
The content of our dissertation relates to idiosyncratic reactions connected with the use of antipsychotic drugs. The below review of articles concerning reaction of idiosyncrasy in the course of treatment with psychotropic drugs brings closer the scale of therapeutic problems during the psycho pharmacotherapy. Idiosyncrasy is an expression used to describe unexpected side effects independent from the drug doses. There are many syndromes of the idiosyncrasy occurring after the drug use. They are described with the following terms: Dress Syndrome (being the syndrome of reaction after drug usage with eosinophilia and systemic symptoms), HHS (Hypersensitivity Syndrome), DIHS (Drug Induced Hypersensitivity Syndrome), DIDMOHS (Drug Induced Multiorgan Hypersensitivity Syndrome) and Drug Induced Pseudolymphoma. The clinical extreme of idiosyncratic reaction is neuroleptic malignant syndrome.